2011
DOI: 10.1371/journal.pone.0027944
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Tissue Microenvironment Can Inhibit Dendritic Cell Maturation in Colorectal Cancer

Abstract: Inflammatory mediators in the tumour microenvironment promote tumour growth, vascular development and enable evasion of anti-tumour immune responses, by disabling infiltrating dendritic cells. However, the constituents of the tumour microenvironment that directly influence dendritic cell maturation and function are not well characterised. Our aim was to identify tumour-associated inflammatory mediators which influence the function of dendritic cells. Tumour conditioned media obtained from cultured colorectal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 36 publications
7
87
3
Order By: Relevance
“…Like other professional APCs, DCs also play a central role in antigen presentation and activation of naive T cells, and they both can initiate and modulate immune responses as a function of exogenous stimuli (39). Alteration of DC function is one of the various strategies developed by malignant cells to escape immune elimination (40). In a trypanosome infection, DCs play a crucial role in the activation of Th-cell responses, with DCs being the primary cell population inducing a VSG-specific response in naive T cells (15).…”
Section: Discussionmentioning
confidence: 99%
“…Like other professional APCs, DCs also play a central role in antigen presentation and activation of naive T cells, and they both can initiate and modulate immune responses as a function of exogenous stimuli (39). Alteration of DC function is one of the various strategies developed by malignant cells to escape immune elimination (40). In a trypanosome infection, DCs play a crucial role in the activation of Th-cell responses, with DCs being the primary cell population inducing a VSG-specific response in naive T cells (15).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that conditioned media from explant tissue, which more accurately represents the tumor microenvironment including the different cell subtypes within the tumor, inhibit dendritic cell maturation and function (6). We found that TCM of explant tissues inhibit dendritic cell maturation by reducing the expression of CD80, CD54, CD86, HLA-DR, CD1d, and CD83, while also increasing IL-10 and decreasing IL-12p70 secretion.…”
Section: Discussionmentioning
confidence: 80%
“…All tissue was obtained with the written informed consent of the patient, and the study protocol was approved by the Ethics Committee at St. Vincent's University Hospital. The explanted tissue was cut into 8 equal sized pieces of approximately 5 mm 3 and cultured as previously described (6,13). Briefly, the explanted tumor tissues were either untreated or treated with 100 mg/mL bevacizumab (Avastin) and cultured for 72 hours (in 24-well plates) in 2 mL RPMI-1640 containing 100 U/mL penicillin, 100 mg/mL streptomycin, 4 mg/mL Fungizone, 30 mg/mL gentamicin (Invitrogen), and supplemented with 20% FBS (Invitrogen).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role played by DCs in CRC is controversial due to the fact that some studies have found that tumor cells are able to impair the function of these cells in inducing an effective immune response capable of eliminating transformed cells. In this direction, tissue culture media from CRC explants inhibit DC maturation with reduced levels of CD54, CD86, HLA-DR, and CD83, and induce IL-10 secretion while inhibiting secretion of IL-12p70, factors that inhibit Th1 immune responses and probably protect the tumor from a potent immune response [ 125 ]. Moreover, in vivo DCs infi ltrating the tumor show an immature phenotype [ 126 ] and those immature DCs correlate with infi ltration by Treg cells and with no detectable tumor-associated antigen systemic response [ 89 ].…”
Section: Cancer Microenvironment and Immunosuppressionmentioning
confidence: 99%